2016
DOI: 10.1515/pjct-2016-0041
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic removal of reactive yellow 145 dye from simulated textile wastewaters over supported (Co, Ni)3O4/Al2O3 co-catalyst

Abstract: The supported co-catalyst (Co, Ni) 3 O 4 /Al 2 O 3 was prepared via using a co-precipitation method. Three sets of these materials were prepared by calcination at three different temperatures 500, 600, and 700 o C. Crystal structure of the prepared materials was investigated using powder X-rays diffraction (PXRD), Fourier transform infrared spectroscopy (FTIR), Atomic force microscope (AFM), and specifi c surface area (BET). The activity of the prepared catalysts was investigated by following both of photocata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…The effect of silver decorated nanoparticles was a decrease of the possibility The obtained rate constant for Reactive Blue 250 using Zn 0.5 Ca 0.5 Fe 2 O 4 (sol-gel)/Ag (photodeposition) nanoparticles was similar to the reported value (k = 0.0885 min −1 ) for Reactive Blue 4 using pure anatase nano-TiO 2 under UV light [39]. Regarding RY145, the degradation rates were much lower but were higher than the value reported for this dye using a Ni 3 O 4 -Co 3 O 4 /Al 2 O 3 catalyst when pseudo-first-order kinetics was followed (k = 0.01623 min −1 ) [40]. The different degradation rates of the two reactive azo dyes must be related to chemical structure variations, as already observed in the photodegradation of azo dyes using ZnO nanoparticles [41].…”
Section: Photodegradation Assayssupporting
confidence: 87%
“…The effect of silver decorated nanoparticles was a decrease of the possibility The obtained rate constant for Reactive Blue 250 using Zn 0.5 Ca 0.5 Fe 2 O 4 (sol-gel)/Ag (photodeposition) nanoparticles was similar to the reported value (k = 0.0885 min −1 ) for Reactive Blue 4 using pure anatase nano-TiO 2 under UV light [39]. Regarding RY145, the degradation rates were much lower but were higher than the value reported for this dye using a Ni 3 O 4 -Co 3 O 4 /Al 2 O 3 catalyst when pseudo-first-order kinetics was followed (k = 0.01623 min −1 ) [40]. The different degradation rates of the two reactive azo dyes must be related to chemical structure variations, as already observed in the photodegradation of azo dyes using ZnO nanoparticles [41].…”
Section: Photodegradation Assayssupporting
confidence: 87%
“…8, which show the increasing catalytic activity of dye decolorization by increasing the amount of catalyst from 0.02 to 0.08 g. Possibly, this is due to the increasing of active sites number on the surface of catalyst and then increasing the decolorization of dye. Increasing the catalyst [18][19][20] by the agglomeration of catalyst particles (increasing the turbidity). This can lead to light scattering and prevent it from transmitted to the inner reaction mixture which leads to a decrease in the efficiency of CBB dye over the used catalyst [21].…”
Section: Decolorization Efficiency Of Cbb Dye Over Different Weights mentioning
confidence: 99%
“…Also different modified forms of these photocatalyst include doped oxides with metals and non-metals, activated carbons/photocatalysts and coupled oxides [8,9]. On other hand, both of single MgO and Ni3O4 was used in treatment of polluted industrial wastewaters in heterogeneous photocatal-ysis systems and it was found that these polluted dyes in the polluted wastewaters were mineralized into CO2, H2O and some other volatile and inorganic materials [10,11].…”
Section: Photocatalytic Decolorization Of Celestine Blue B From Indusmentioning
confidence: 99%